PESAN DAKWAH DALAM LINE WEBTOON “KOLANG-KALING” EPISODE SEMBILAN (9) - Sunrise (EDISI RAMADHAN 2021) - Hadi Ismanto; Nor Azizah Safitri (Program Studi Komunikasi dan Penyiaran Islam Pascasarjana UIN KHAS Jember, 2021)
Various media can be used in the implementation of da'wah, such as comics. In the month Ramadhan 2021, LINE Webtoon published a new webtoon with the title